Analysis of Erythrocyte Invasion Mechanisms of Plasmodium falciparum Clinical Isolates Across 3 Malaria-Endemic Areas in Ghana. (2nd April 2015) - Mensah-Brown, Henrietta E.; Amoako, Nicholas; Abugri, James; Stewart, Lindsay B.; Agongo, Godfred; Dickson, Emmanuel K.; Ofori, Michael F.; Stoute, José A.; Conway, David J.; Awandare, Gordon A.
Abstract: Background. Plasmodium falciparum invades human erythrocytes by using an array of ligands that interact with several receptors, including sialic acid (SA), complement receptor 1 (CR1), and basigin. We hypothesized that in malaria-endemic areas, parasites vary invasion pathways under immune pressure. Therefore, invasion mechanisms of clinical isolates collected from 3 zones of Ghana with different levels of endemicity (from lowest to highest, Accra, Navrongo, and Kintampo) were compared using standardized methods. Methods. Blood samples were collected from children aged 2–14 years in whom malaria was diagnosed, and erythrocyte invasion phenotypes were determined using the enzymes neuraminidase, chymotrypsin, and trypsin, which differentially cleave receptors from the erythrocyte surface. In addition, antibodies against CR1 and basigin were used to determine the contributions of these receptors to invasion. Gene expression levels of P. falciparum invasion ligands were also examined. Results. The parasites generally expressed SA-independent invasion phenotypes across the malaria-endemic areas, with parasites from Kintampo showing the highest invasion rates in neuraminidase-treated erythrocytes. CR1 was a major mediator of SA-independent invasion, while basigin was essential for both SA-dependent and SA-independent invasion mechanisms. Furthermore, expression of the basigin ligand PfRh5 was the best predictor of donor parasitemia. Conclusions. Erythrocyte invasion phenotypes expressed by P. falciparum are influenced by endemicity levels, and the PfRh5-basigin pathway is a potential vaccine target.